1978
DOI: 10.1007/bf00495765
|View full text |Cite
|
Sign up to set email alerts
|

Cytochemical investigations on the localization of 5?-nucleotidase in the rat hippocampus with special reference to synaptic regions

Abstract: The fine structural localization of the 5'-nucleotidase was investigated in the CA3 region of the rat hippocampus. The attention was focussed on the occurrence of the enzyme in the synaptic region. The 5'-nucleotidase activity was demonstrated at the surface membranes of axons and dendrites. Prominent portions of enzyme activity were detectable in the nuclei and the nuclear envelope, whereas the cytoplasmic organelles were nearly devoid of reaction product. In synapses five types of 5'-nucleotidase localizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

1984
1984
2014
2014

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(18 citation statements)
references
References 23 publications
2
16
0
Order By: Relevance
“…5′Nucleotidases in particular were found at the surface membranes of axons and dendrites (Bernstein et al, 1978) and are associated with glial membranes in the central nervous system (Schoen & Graybiel, 1992). Localization of ecto-Ca-ATPase and 5′-ectonucleotidase activities was shown in caveolae of smooth muscle cells of the guinea-pig vas deferens and their role in neurotransmission has been suggested (Kittel & Bacsy, 1994).…”
Section: Termination Of Neurotransmitter Actionmentioning
confidence: 99%
“…5′Nucleotidases in particular were found at the surface membranes of axons and dendrites (Bernstein et al, 1978) and are associated with glial membranes in the central nervous system (Schoen & Graybiel, 1992). Localization of ecto-Ca-ATPase and 5′-ectonucleotidase activities was shown in caveolae of smooth muscle cells of the guinea-pig vas deferens and their role in neurotransmission has been suggested (Kittel & Bacsy, 1994).…”
Section: Termination Of Neurotransmitter Actionmentioning
confidence: 99%
“…5'-Nucleotidase has been shown by a number of researchers to be an enzyme closely associated with myelin [Naidoo, 1962;Banik and Davison, 1969;Kreutzberg et al, 1978;Bernstein et al, 1978;Cammer et al, 1980;Cammer andZimmerman, 1981a, 1981b;Smith et al, 1980;Shanker et al, 19821. Recent in vivo studies have shown that 5'-nucleotidase is localized in myelin, in the distal process of oligodendroglia, and in the oligodendroglial expansions surrounding the myelin sheath [Vercelli-Retta et al, 1976;Kreutzberg et al, 1978;Cammer et al, 19801.…”
Section: Introductionmentioning
confidence: 99%
“…To learn more about a possible connection between neuronal localization of both transporter proteins and this particular type of neuromodulation, we compared the distribution of ABCB1 and ABCC1 with those of 5-N´ ADA and NTPDase2. Since all three enzymes are important regulators of purinergic cell signalling (Burnstock, 2013; Gampe et al, 2012; Kulesskaya et al, 2013; Mutafova-Yambolieva and Durnin, 2014) by degrading ATP (5-N´ degrades 5´-AMP to adenosine, ADA degrades adenosine to inosine and NTPDase2 hydrolyses extracellular nucleoside triphosphates to nucleoside monophosphates) they have repeatedly been used as putative marker enzymes to anatomically localize adenosinergic/purinergic neuromodulation (Bernstein et al, 1978; Kulesskaya et al, 2013; Staines et al, 1988; Yamamoto et al, 1987)). However, due to their wide distribution within the brain ((Burnstock et al, 2011); this study) the immunodetection of 5´-N and/or ADA in a specific brain cell compartment does not unequivocally prove the presence of purinergic/adenosinergic neuromodulation).…”
Section: Discussionmentioning
confidence: 99%